Make a virtue of necessity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Practical handbook on cane rat domestication YDC Extension Series No 2, Youth Development Centre (YDC), Cameroon, 2001. 33 pp. US$ 10 Euro 10.15